Influence of smoking with smoke flavorings on the oxidative stability of farmed sea bass fillets monitored by 1H NMR and FTIR. Issue 4 (16th September 2016) - Vidal, Natalia P.; Manzanos, María J.; Goicoechea, Encarnación; Guillén, María D.
Abstract : Farmed European sea bass ( Dicentrarchus labrax ) fillets were smoked with three commercial smoke flavorings. Unsmoked and smoked fillets were submitted to oxidative conditions to study their oxidative stability. To this aim, at regular intervals of time under oxidative conditions, their lipids were extracted and studied by Fourier transform mid‐infrared spectroscopy (FTIR) and Proton nuclear magnetic resonance ( 1 H NMR). Both kinds of spectra provide markers referred to the beginning and extension of the lipid degradation and of the formation of new compounds resulting from the oxidation process. Obtaining these data from FTIR is easier, simpler, and quicker than it is from 1 H NMR, but this latter technique provides, simultaneously, additional interesting information about the sample. The increase of the oxidative stability of sea bass fillets as a consequence of smoking is proved, as well as the influence on this increase of the concentration of certain phenolic smoke components in the fillets. Practical applications: Farmed European sea bass is widely available in the market, in some occasions the supply being greater than the demand. This study could be very interesting for the seafood industry, because smoking of sea bass fillets with smoke flavorings not only extends their shelf‐life, but also provides them with special sensory characteristics, diversifying its presence in the market as a new ready‐to‐eat product. Nevertheless, it must be taken into account that not all the smoke flavorings show the same effect on fish. This study demonstrates that the smoke flavoring composition and its application method have a great influence on the oxidative stability of smoked sea bass fillets. A study of the lipid oxidative stability of unsmoked and smoked sea bass fillets with three different commercial smoke flavorings was undertaken. To this aim, unsmoked and smoked sea bass fillets were submitted to oxidative conditions and their lipids were extracted and analyzed by Fourier transform infrared spectroscopy (FTIR) and Proton nuclear magnetic resonance ( 1 H NMR) periodically. Abstract : A study of the lipid oxidative stability of unsmoked and smoked sea bass fillets with three different commercial smoke flavorings was undertaken. To this aim, unsmoked and smoked sea bass fillets were submitted to oxidative conditions and their lipids were extracted and analyzed by Fourier transform infrared spectroscopy (FTIR) and Proton nuclear magnetic resonance ( 1 H NMR) periodically.